A differential effect of E. coli toxin-antitoxin systems on cell death in liquid media and biofilm formation. - Ilana Kolodkin-Gal (Public Library of Science (PLoS), 2009)
Toxin-antitoxin (TA) modules are gene pairs specifying for a toxin and its antitoxin and are found on the chromosomes of many bacteria including pathogens. Here we report how each of five such TA systems in E. coli affect bacterial cell death differently in liquid media and during biofilm formation. Of all these systems, only the TA system mazEF mediated cell death both in liquid media and during biofilm formation. At the other extreme, as our results have revealed here, the TA system dinJ-YafQ is unique in that it is involved only in the death process during biofilm formation. Cell death governed by mazEF and dinJ-YafQ seems to participate in biofilm formation through a novel mechanism.